Strategi Komunikasi DPMPTSP Kota Serang dalam Memberikan Pelayanan Publik - Nuril Anwar Sutisna; Eka Susilawati; Fithrotul Kamilah; Noerma Kurnia Fajarwati; Arfian Suryasuciramdhan (Pusat Riset dan Inovasi Nasional, 2026)
. This study aims to analyze the communication strategy of the Serang City Investment and One-Stop Integrated Services Agency (DPMPTSP) in providing public services to the community, as well as identifying supporting and inhibiting factors in its implementation. This study uses a qualitative method with a descriptive approach. Primary data were obtained through in-depth interviews, observation, and documentation, while secondary data were collected from literature, regulations, and related official sources. The focus of the study is directed at the application of the two-way symmetrical communication theory that emphasizes interactive dialogue, feedback acceptance, communication equality, and active community participation. The results show that the Serang City DPMPTSP implements various communication strategies, including delivering information face-to-face and digitally (website, social media, and SKM barcodes), providing complaint channels, and involving the community in service evaluation. Supporting factors include the availability of service facilities, competent human resources, and information technology support. Inhibiting factors include limited digital literacy in the community, technical system obstacles, and differences in the level of public understanding of service procedures.